Manajemen Sumber Daya (Biaya Dan Sarana Prasarana) Lembaga Pendidikan Islam - Nabilla Azzahwa (Journal Islamic Education, 2025)
Infrastructure facilities are an important place for continuity in Islamic educational institutions. This research aims to: 1) analyze the planning, maintenance, and inventory and elimination of infrastructure facilities to support the learning process, 2) get to know more about the management of financing infrastructure facilities of Islamic educational institutions. This research method uses a qualitative approach, this type of study is a field study with interview techniques, observation, documentation. This study found that optimizing the management of costs and infrastructure facilities is very important to support the sustainability and improvement of the quality of Islamic educational institutions such as implementation carried out sequentially from planning, maintenance, inventorying, and elimination which is carried out properly and regularly. Integration with Islamic values can also be a distinctive feature and advantage of Islamic educational institutions.